2008
DOI: 10.1200/jco.2007.14.0988
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Pharmacokinetic and Pharmacodynamic Study of the Oral Mammalian Target of Rapamycin Inhibitor Everolimus in Patients With Advanced Solid Tumors

Abstract: Everolimus was satisfactorily tolerated at dosages up to 70 mg/wk and 10 mg/d with predictable PK. Antitumor activity and PD in tumors require further clinical investigation. Doses of 20 mg/wk and 5 mg/d are recommended as appropriate starting doses for these studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
345
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(382 citation statements)
references
References 29 publications
35
345
1
1
Order By: Relevance
“…This assumption has had huge clinical implications as phospho-S6 or phospho-S6K1 is often utilized in rapamycin-based clinical studies to measure in vivo inhibition of mTORC1. 26,27 In contrast to these assumptions, we recently reported that rapamycin differentially regulated S6Ks versus 4E-BP1. 4 While rapamycin inhibited S6K1 in all cell lines that were tested, the phosphorylation of 4E-BP1 was differentially controlled relative to the cell type.…”
Section: Differential Regulation Of S6ks Versus 4e-bp1mentioning
confidence: 85%
“…This assumption has had huge clinical implications as phospho-S6 or phospho-S6K1 is often utilized in rapamycin-based clinical studies to measure in vivo inhibition of mTORC1. 26,27 In contrast to these assumptions, we recently reported that rapamycin differentially regulated S6Ks versus 4E-BP1. 4 While rapamycin inhibited S6K1 in all cell lines that were tested, the phosphorylation of 4E-BP1 was differentially controlled relative to the cell type.…”
Section: Differential Regulation Of S6ks Versus 4e-bp1mentioning
confidence: 85%
“…Dose-limiting toxicities (DLTs) observed at 70 mg included grade 3 stomatitis, neutropenia, and hyperglycaemia (Tabernero et al, 2008). Consistent inhibition of S6K1 activity in peripheral blood mononuclear cells was seen with doses X20 mg per week and was sustained for at least 7 days at doses X20 mg per week (O'Donnell et al, 2008). Furthermore, immunohistochemical analysis in paired tumour tissue biopsies taken before and during weekly dosing (20, 50, or 70 mg) confirmed inhibition of S6K1 at doses X20 mg (Tabernero et al, 2008).…”
mentioning
confidence: 96%
“…Everolimus displays direct effects on growth and proliferation of cancer cells and inhibits angiogenesis by preventing the proliferation of endothelial cells in human tumour xenografts (Beuvink et al, 2001;Lane et al, 2003). In single-agent phase I studies of everolimus performed in patients with advanced cancers, a safe toxicity profile along with evidence of sustained tumour stabilisation at weekly doses of 10 -70 mg was shown (O'Donnell et al, 2008;Tabernero et al, 2008). Dose-limiting toxicities (DLTs) observed at 70 mg included grade 3 stomatitis, neutropenia, and hyperglycaemia (Tabernero et al, 2008).…”
mentioning
confidence: 99%
“…mTOR inhibitors reduce VEGF synthesis through A phase I study reported mean plasma C max of 61ng/ml with an everolimus dosing schedule of 10mg per day, and mean plasma C max of 174ng/ml with a dosing schedule of 70mg per week [174]. The effects of everolimus were therefore studied over a dose range of 0 -250ng/ml.…”
Section: Mtor Inhibitionmentioning
confidence: 99%